Peace through history? The Carnegie Endowment for International Peace's inquiry into European schoolbooks, 1921–1924. Issue 1 (2nd January 2016) - Irish, Tomás
Abstract : In 1924 the Carnegie Endowment for International Peace published a volume investigating the teaching of school history in former belligerent states in Europe. The project sought to reconcile former enemies through mutual understanding and educational exchange and reflected a widely held belief that although the military conflict had finished, its ideas still resounded and served to perpetuate antagonism. The CEIP project, conceived in the internationalist spirit, was itself derailed by nationalist enmity, a consequence of the Franco-Belgian occupation of the Ruhr in January 1923, demonstrating the limits of cultural reconciliation in the early 1920s, and the resultant volume showed that belligerent views of recent history were still being taught to schoolchildren in France and Germany in the early 1920s.